2012
DOI: 10.1177/1046496412440055
|View full text |Cite
|
Sign up to set email alerts
|

Time Pressure Affects Process and Performance in Hidden-Profile Groups

Abstract: In the present experiment, members of three-person groups read information about two hypothetical cholesterol-reducing drugs and collectively chose the better drug under high or low time pressure. Information was distributed to members as a hidden profile such that the information that supported the better drug was unshared before discussion. Correct solution of the hidden profile required members to pool their unshared knowledge. Some groups discussed the drug information from memory (memory condition). Other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…These results are in line with prior studies (Bowman and Wittenbaum 2012;Steinel, Utz, and Koning 2010) also challenging the generalisability of the information sampling bias (Stasser and Titus 1985;Stasser, Vaughan, and Stewart 2000).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are in line with prior studies (Bowman and Wittenbaum 2012;Steinel, Utz, and Koning 2010) also challenging the generalisability of the information sampling bias (Stasser and Titus 1985;Stasser, Vaughan, and Stewart 2000).…”
Section: Discussionsupporting
confidence: 91%
“…The practical justification for considering time pressure is that in our fast-paced society, people often have to make decisions under time pressure, and especially then the sharing of tacit or private information would be relevant. From a theoretical perspective, previous research has shown that time pressure lowers decision quality in groups, in the laboratory as well as in actual teams (Bowman and Wittenbaum 2012;Chong et al 2012;De Dreu 2003), supposedly because time pressure increases the need for cognitive closure (NFCC), that is, the desire to reach quick decisions in ambiguous situations (Webster and Kruglanski 1994). Moreover, the motivated information processing in groups (MIP-G) model predicts that social motivation and epistemic motivation such as NFCC, separately and, most importantly, in interaction, affect information processing and sharing in groups.…”
Section: Introductionmentioning
confidence: 99%
“…Teams thus make suboptimal decisions in hidden profile situations. These problems only intensify when teams face a wealth of information or have to decide under time pressure (Stasser and Titus, 1987;Bowman and Wittenbaum, 2012;Lu et al, 2012;Mesmer-Magnus et al, 2011). Both of these challenges are common during crises.…”
Section: Deliberating Efficiently In Times Of Crisismentioning
confidence: 99%
“…Third, following previous contextual studies on information sharing: leadership style (Larson, et al, 1998), task features (Greitemeyer et al, 1998): temporal features (Bowman, et al, 2012), communication technology (Jimenez-Rodriguez, 2012), functional diversity (Xiao et al, 2016), separatist group orientation (Kolb, Swol, 2018), group structure and composition (Postmes, Spears, Cihangir, 2001), member characteristics (Cruz, et al, 1999) and discussion procedures (Savadori, et al, 2001): we added a new contextual research. In view of the fact that there exist risks in the process of communication, this paper introduced TPS into team information sharing for the first time, confirming that it is beneficial to team information sharing and it is more conducive to unique information sharing than common information sharing.…”
Section: Theoretical Contributionsmentioning
confidence: 99%